Utilization of Root-Colonizing Bacteria to Protect Hot-Pepper Against Tobacco Mosaic Tobamovirus - TRI ASMIRA DAMAYANTI; HENDRA PARDEDE; NISA RACHMANIA MUBARIK (Bogor Agricultural University, Indonesia, 2007)
Tobacco Mosaic Tobamovirus (TMV) is one of many important viruses infecting Solanaceous plants including hot pepper in Indonesia. To accomplish and improve the effectiveness of virus management, we used root-colonizing bacteria (rhizobacteria) isolated from healthy hot pepper. Eight rhizobacteria isolates were selected and their capacity in enhancing plant growth and inducing systemic resistance (ISR) against TMV in greenhouse trials were evaluated. The rhizobacteria was applied as seed treatment and soil drench. Bacterized-seedling showed a better growth vigor, fitness and a milder symptom than non-bacterized control plants. The protective effect of rhizobacteria was more pronounced after challenging inoculation by TMV, especially for plants treated by isolates I-6, I-16, and I-35. However, TMV accumulation was slightly affected by bacterial treatment. The rhizobacteria might improved ISR by increasing peroxidase enzyme activity but this depends on the species. Based on whole results, isolate I-35 was the potential plant growth promotion rhizobacteria (PGPR). The I-35 was identified as Bacillus cereus based on morphological characteristics and nucleotide sequences of 16S r-RNA. Key words: root-colonizing bacteria, TMV, ISR